Water contamination emergencies : collective responsibility - Gray, J. 1947-; Thompson, K. C. 1944- (Special publication (Royal Society of Chemistry (Great Britain)), 2009)
By leading experts, this is an up-to-date view of the strategies essential for an effective response to water contamination emergencies.